PERAN KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGEMBANGAN DI NAGARI KOTO KACIAK, KECAMATAN TANJUNG RAYA, KABUPATEN AGAM, SUMATERA BARAT - Hayati Husna; Gusril Basir (ADISAM PUBLISHER, 2024)
Tourism awareness groups (Pokdarwis) play a role as a driver of tourism awareness, increase understanding of tourism, and succeed in tourism development. They also aim to improve the position and role of the community as an important object in tourism development, as well as introduce, preserve, and utilize the potential of tourist attractions in their respective regions. Nagari Koto Kaciak has a wealth of natural, cultural, and historical heritage that is a great tourism potential. The Nagari Koto Kaciak Tourism Awareness Group (Pokdarwis) is supported by Agam Regency's policy in developing tourism at the Nagari level. They play an institutional role at the community level consisting of tourism actors who support tourism development and improve the welfare of the surrounding community. One of the challenges faced is the lack of movement of the tourism sector which is characterized by the low number of tourist visits and thus affects MSMEs in the surrounding community. The Nagari Koto Kaciak Tourism Awareness Group (Pokdarwis) continues to make efforts to improve the quality of human resources of its members to develop tourism for the benefit of the community, society, attracting tourists through facilitative roles, educational roles, representational roles, and technical roles. The purpose of this study is to analyze the role of tourism awareness groups (Pokdarwis) in tourism development in Nagari Koto Kaciak, Tanjung Raya District, Agam Regency using qualitative methods. The results of this study show that the role of tourism awareness groups (Pokdarwis) affects the development of Nagari Koto Kaciak tourism. A facilitative role that provides the community with employment and investment advice. The role of education is carried out by embracing the community to participate in training to meet the needs of the community. The role of representation is to establish working relationships internally and externally to innovate the development of Nagari Koto Kaciak tourism. The technical role in the use of technological tools and carrying out management aspects, namely planning for the development of tourist destinations, organizing is carried out by dividing tasks according to division responsibilities, actuating managing tourism potential, and controlling by monitoring Nagari Koto Kaciak tourism.